Some marine leeches and first record of Branchellion torpedinis Savigny, 1822 (Annelida, Hirudinea, Piscicolidae) from elasmobranchs in Turkish waters, with new host records - Basusta, Nuri; De Meo, Ilaria; Miglietta, Claudia; Mutlu, Erhan; Olguner, M. Tunca; Sahin, Ahmet; Patania, Analisa (Springer Heidelberg, 2016)
Three species of marine leeches, Branchellion torpedinis Savigny, 1822, Pontobdella muricata (Linnaeus, 1758), and Stibarobdella moorei (Oka, 1910), were collected from Pteromylaeus bovinus (Geoffroy Saint-Hilaire, 1817), Dasyatis pastinaca (Linnaeus, 1758), and Raja miraletus Linnaeus, 1758, respectively, captured during a cruise aboard the R/V Akdeniz SU from depths of 10, 75 and 125 m in Antalya Bay, on the eastern Mediterranean coast of Turkey. Of these marine leeches, Branchellion torpedinis is recorded for the first time from Turkish waters on a new elasmobranch host, P. bovinus. In addition, R. miraletus is a new host record for Stibarobdella moorei, and Pontobdella muricata is recorded for the second time on its previously known host, D. pastinaca, from Antalya Bay.
Keywords: Branchellion torpedinis; Pontobdella muricata; Stibarobdella moorei; Marine leech; Antalya Bay; Eastern Mediterranean